PERIODONTAL DISEASE STATUS AMONG ADULT POPULATIONATTENDING PRIVATE DENTAL HOSPITALAT GADAP TOWN KARACHI - Raza Abbas et al (Baqai Journal of Health Sciences)
The purpose of this study was to evaluate the periodontal disease status among adult population of private dental clinic of outpatient department Karachi. It was descriptive cross sectional study. A brief study protocol was explained and verbal Informed consent was obtained from each study participants before the oral examination. The examination of oral cavity was carried out according to the World’s Health Organization oral health survey form (1997) using an examination instruments and CPITN probe under proper light source. The data was analyzed by using statistical package for social sciences SPSS 20 version. A total of 104 study participants. The mean age was 2.09 and standard deviations showed 0.837, along with the three age groups were 20-25 (30.8%), 26-35 (29.8%), and 36-45 (39.4%). However, the individuals were doing private job were 44.2%, governments job peoples was 14.4%, businessman persons were 1.9%, jobless individuals were 4.8%, those women’s are housewives were 32.7% and other jobs doing participants like tailor, labor-man, shopkeepers etc., were 1.9%. According to the community periodontal index (CPI) the patients who had diagnosed with bleeding gums were 22.1% this result showed that gingivitis was seen in this rural community of Gadap town, likewise, those patients who attended the dental hospital OPD that have a poor oral hygiene noticed that plaque and calculus deposition was seen during the oral examination were 52.9%. A few personnel who attended the dental clinic in the hospital they had a periodontal pocket depth 4-5mm and gingivitis were 3.8%.